An Approch based on Genetic Algorithm for Multi-tenant Resource Allocation in SaaS Applications - Elaheh kheiri; Mostafa Ghobaei Arani; Alireza Taghizadeh (Institute of Advanced Engineering and Science, 2017)
In recent years, the use of cloud services has been significantly expanded. The providers of software as a service employ multi-tenant architectures to deliver services to their users. In these multi-tenant applications the resource allocation would suffer from over-utilization or under-utilization issues. Considering the significant effects of resource allocation on the service performance and cost, in this paper we have proposed an approach based on genetic algorithm for resource allocation which guarantees service quality through providing adequate resources. The proposed approach also improves system performance, meets the requirements of users and provides maximum resource efficiency. Simulation results show that the proposed approach has better response rate and availability comparing to other approaches, while provides an efficient resource usage.